PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF THE FORMATION OF MORAL VALUES IN ADOLESCENT LEARNERS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article examines the pedagogical and psychological features of the formation of moral values in adolescent learners. Drawing on an empirical study conducted among 60 fifth- and sixth-grade pupils, the author analyses the relationship between the formation of moral values and two closely connected variables — the appraisal of moral behaviour and the level of moral motivation. The study establishes statistically significant positive correlations between these phenomena (r = 0.43 and r = 0.58, p ≤ 0.01) and demonstrates, through a formative experiment, that a purpose-built psychological training programme produces a significant increase in the level of moral-value formation in the experimental group (t = 7.36, p ≤ 0.05). The findings confirm that moral values develop across adolescence in stages and can be strengthened through targeted psychological-pedagogical intervention. The article concludes with practical recommendations for organising the educational process in unity with moral-upbringing tasks.